Analisis Strategi Pemasaran Pada Kedai Madu Tawon Mr. Ipin Dalam Meningkatkan Kepercayaan Dan Kepuasan Kosumen - Mukhamat Nasikin; M. Pudail; Purwanto Purwanto; Yeny Fitriyani (STIE AMKOP, 2023)
The purpose of this study was to find out about the strategy carried out by the wasp honey shop mr. ipin to provide customer trust and satisfaction with qualitative methods with SWOT analysis. SWOT analysis is an assessment of the situation, in determining conditions categorized as strengths, weaknesses, opportunities or threats. The results showed that the word of mouth marketing strategy carried out had a major influence on consumer trust and consumers were satisfied with the experience and quality of honey obtained. The word of mouth strategy has advantages for the company, because it can increase customer interest in buying the honey product Keywords: strategi pemasaran, SWOT, madu